Non-tariff distortions of Australian trade - Lloyd, P. J. (Canberra : Australian National University Press, 1973)
This study provides a view of non-tariff instruments in Australia over a short period which has not been available before. The descriptions relate to non-tariff instruments as of mid-1972
Bibliography: p. 232-236.
osc 23/05/2018
Loans
Keywords: Foreign trade regulation; Australia; Australia